2015
DOI: 10.18553/jmcp.2015.21.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hypoglycemia and Fall-Related Events in Type 2 Diabetes Mellitus: Analysis of a U.S. Commercial Database

Abstract: BACKGROUND: Hypoglycemia is a major barrier to achieving optimal glycemic control and managing diabetes successfully in patients with diabetes. Falls are the most significant consequences caused by hypoglycemia episodes. Both hypoglycemia and falls lead to substantial economic burden on the health care system in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 36 publications
1
49
0
3
Order By: Relevance
“…The multiple and well-recognized complications of long-standing diabetes mellitus include peripheral neuropathy, diabetic retinopathy, autonomic neuropathy, and hypoglycemia from inappropriate glycemic control, all of which can significantly contribute to the risks of falls through multiple mechanisms (Morley, 1999). Recently, Kachoo et al (2015) showed that the risk of fall-related events increased 2-fold among elderly diabetic patients who experienced hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple and well-recognized complications of long-standing diabetes mellitus include peripheral neuropathy, diabetic retinopathy, autonomic neuropathy, and hypoglycemia from inappropriate glycemic control, all of which can significantly contribute to the risks of falls through multiple mechanisms (Morley, 1999). Recently, Kachoo et al (2015) showed that the risk of fall-related events increased 2-fold among elderly diabetic patients who experienced hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…DM promotes peripheral nerve dysfunction and is a frequent cause of falls (29), although vitamin D 3 treatment reportedly plays a role in preventing falls (22). Thus, we hypothesized that Schwann cells were critical targets of DM and that vitamin D 3 might regulate their activity.…”
Section: High Glucose Concentrations Induce Schwann Cellmentioning
confidence: 97%
“…Hypoglycaemia is one of the main complications of diabetes treatment and is associated with serious adverse events (12). The majority of studies exploring the association between hypoglycaemic events and fracture risk have used commercial health claims databases (13,14,15) or national hospital and psychiatric registers (16). The latter patients constitute a distinct subset and these findings may not be applicable to the general diabetic population.…”
Section: Introductionmentioning
confidence: 99%